1995
DOI: 10.1128/aem.61.2.793-796.1995
|View full text |Cite
|
Sign up to set email alerts
|

A critical examination of the specificity of the salkowski reagent for indolic compounds produced by phytopathogenic bacteria

Abstract: We examined the sensitivity and the specificity of three versions of the Salkowski colorimetric technique. Two of these allowed the detection of indoleacetic acid (IAA) over a low range of concentrations (0.5 to 20 g/ml), while the third permitted the detection of IAA over a range of higher concentrations (5 to 200 g/ml). Overall, the three formulations reacted not only with auxin (IAA) but also with indolepyruvic acid and indoleacetamide. Therefore, these techniques appear to be specific for IAA, indolepyruvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
409
1
20

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 929 publications
(436 citation statements)
references
References 13 publications
6
409
1
20
Order By: Relevance
“…We found that R. radiobacter (PABac-DSM) produces IAA in the presence of tryptophan. Despite the fact that Salkowski reagent also detects indole pyruvic acid and indole acetamide in addition to IAA (Glickmann and Dessaux, 1995), the method is fairly accurate because IAA is usually known as the main excreted microbial auxin. IAA is best known for its role in plant signal transduction (Quint and Gray, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…We found that R. radiobacter (PABac-DSM) produces IAA in the presence of tryptophan. Despite the fact that Salkowski reagent also detects indole pyruvic acid and indole acetamide in addition to IAA (Glickmann and Dessaux, 1995), the method is fairly accurate because IAA is usually known as the main excreted microbial auxin. IAA is best known for its role in plant signal transduction (Quint and Gray, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous plant-associated bacteria are able to produce auxin (3-indoleacetic acid [IAA]), a plant hormone of broad influence on plant growth and development, such as root architecture, vascular differentiation, and disease signaling, among many others. This assay, based on the Glickmann and Dessaux (1995) method, is used to measure the total amount of indolic compounds produce by a bacterial strain. However, it is not able to separate the amount of each "putative" indolic compound present in a sample (as IAA, indole-3-acetyl-trytophan [IA-Trp], indole-3-acetyl-aspartic acid [IA-Asp], and indole-3-acetyl-glutamic acid [IA-Glu] conjugates).…”
Section: Indolic Compound Production Assaymentioning
confidence: 99%
“…Previous experiments (S. Taghavi, unpublished results) have shown that Enterobacter sp. 638 is only able to produce low levels of IAA, <4 lg mL À1 after 48 h incubation with tryptophan under standard culture conditions (Schatz & Bovell, 1952;Glickmann & Dessaux, 1995). When grown in mineral media, Enterobacter sp.…”
Section: Introductionmentioning
confidence: 99%